ANALISA RISIKO KESELAMATAN KERJA DENGAN MENGGUNAKAN METODE HAZARDS IDENTIFICATION, RISK ASSESSMENT AND RISK CONTROL (HIRARC) dI LABORATORIUM BTPLDD PTLR BATAN SERPONG BANTEN - Wawan Sulistyo; Winardi Dwi Nugraha; Arie Budianti (Departemen Teknik Lingkungan Fakultas Teknik Universitas Diponegoro, 2013)
ABSTRACTThe laboratory is part of the work which carries the risk with other risks from equipment, chemicals, and worker behavior. Dangers that commonly cause harm should be prevented or controlled. These components will be identified types of risks and dangers of the terms of each of the processes that occur in the analytical work in the laboratory. Information from the identification results will be analyzed to determine the level of every source. The results of the analysis and assessment using risk assessment guidelines K3 BATAN which is chosen as the reference standard in this study. Based on the risk assessment of all research activities in the laboratory BTPLDD in October-November 2012 concluded the level risk of BTPLDD laboratory is A, which means the risk is acceptable and effective control measures assessed.